Economical Analysis of Chamomile (Matricaria recutita L.) Cultivars, Flower Yields Which are Obtained from Different Sowing Times and Row Spacing - Doğan Arslan; Önder Volkan Bayraktar; Mükremin Temel; Emine Bayram (Journal of Agricultural Sciences)
This study was conducted with split-split plots experimental design based on four replications in the ecological conditions of Yalova in the area of Ataturk Central Horticultural Research Institute in growing seasons of 2008-2009 and 2010-2011. In the study three chamomile (Matricaria recutita L.) cultivars (Bona, Bodegold and Zloty Lan) and a genotype, which was collected from the flora of Yalova Province, were used as material. There were four cultivars/genotypes, three sowing time (early November, early October, end of October) and four rows spacing (15 cm, 30 cm, 45 cm, 60 cm). Sowing times were constructed to main plots, cultivars/genotypes to sub plots and row spacing to sub-sub plots. The highest gross profit was calculated as 8818.33 € ha-1 in first time of Zloty Lan cultivar at 15 cm row spacing. Although the Yalova genotype has the lowest cost, the gross profit among the cultivars/genotypes has been the lowest genotype.